FOXC1 Expression Predicts Capecitabine Efficacy in Patients with Triple-Negative Breast Cancer from the GEICAM_CIBOMA Trial - Rojo, Federico (2025)
Purpose: In a prespecified GEICAM_CIBOMA trial (NCT00130533) correlative analysis, PAM50 non–basal-like breast cancer (non- BLBC) status distinguished patients with triple-negative breast cancer (TNBC) who are most likely to benefit from adjuvant capecitabine. The standardized forkhead box C1 (FOXC1) IHC test has demonstrated strong reliability in classifying the BLBC subtype throughout TNBC cohorts. This translational analysis aimed to evaluate the prognostic/predictive significance of BLBC classification by FOXC1 IHC in the phase III GEICAM_CIBOMA clinical trial. Experimental Design: Tumor tissues from patients with TNBC randomized to standard (neo)adjuvant chemotherapy followed by capecitabine versus observation were analyzed using the standardized FOXC1 IHC test to assess its BLBC/non-BLBC TNBC subtyping capacity as a distant relapse-free survival clinical outcome predictor of capecitabine benefit (exploratory endpoints: disease-free survival, overall survival, and recurrence-free survival). Results: A total of 705 (80.5%) patients from the GEICAM_ CIBOMA trial were evaluable for FOXC1 expression analysis, with balanced distribution between the trial’s treatments. FOXC1 proportion/intensity (VFOXC1) score–based subtyping demonstrated a strong association [AUC ¼ 0.87; 95% confidence interval (CI), 0.84–0.91] and agreement (κ index ¼ 0.43; P < 0.0001) with PAM50 molecular subtyping. VFOXC1 non-BLBC TNBC subtype was a significant independent predictor of clinical benefit with capecitabine for distant relapse-free survival (HR, 0.44; 95% CI, 0.25–0.76; P ¼ 0.003). This predictive effect of VFOXC1 non-BLBC on capecitabine efficacy was further confirmed at disease-free survival (HR, 0.47; 95% CI, 0.28–0.78; P ¼ 0.003), overall survival (HR, 0.48; 95% CI, 0.24–0.96; P ¼ 0.038), and recurrence-free survival (HR, 0.39; 95% CI, 0.22–0.72; P ¼ 0.002). Conclusions: This ambispective GEICAM_CIBOMA translational analysis validated FOXC1-based basal-like/non–basal-like subtyping as a pragmatic alternative to PAM50 subtyping and independently predicted the benefit of adding capecitabine to standard (neo)adjuvant chemotherapy in TNBC.